Trends in kidney cancer among the elderly in Denmark, 1980–2012. (22nd January 2016) - Azawi, Nessn H.; Joergensen, Simon Moeller; Jensen, Niels Viggo; Clark, Peter E.; Lund, Lars; ,
Abstract: Background The purpose of this study is to elucidate incidence, mortality, survival, and prevalence of kidney cancer in elderly persons compared with younger persons in Denmark. Material and methods Cancer of the kidney was defined as ICD-10 code DC 64. Data derived from the NORDCAN database with comparable data on cancer incidence, mortality, prevalence and relative survival in the Nordic countries, where the Danish data were delivered from the Danish Cancer Registry and the Danish Cause of Death Registry with follow-up for death or emigration until the end of 2013. Results The proportion of patients diagnosed with kidney cancer over the age of 70 years has decreased from 43% in 1980 to 32% in 2012 in men and remained almost constant in women, around 50%. Incidence rates were at least five times higher in men aged 70 years more but there was no particular trend with time. In men aged less than 70 years, the incidence rates started increasing around 2000. The incidence rates were lower in women but with a similar pattern as in men. Mortality rates remained stable over time in persons aged 70 years or more while they decreased with time in younger women. Both the one- and the five-year relative survival increased steadily over time for all age groups but the survival was lower for patients aged 70 years or more than for younger patients. The prevalence increased three times from 1559 patients being alive after kidney cancer in1980 to 4713 in 2012. Conclusion A challenge in managing kidney cancer in the elderly is to establish interdisciplinary collaborations between different specialties, such as surgeons, clinical oncologists, and geriatricians to be able to deliver the best possible care in the future.